The role of social media applications in palm oil extension services in Malaysia - Tan Say Peng; Novel Lyndon; Khairuman Hashim; Zaki Aman (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Malaysian palm oil industry faces many challenges, especially in agricultural technology at the plantation level because smallholders have trouble getting detailed information and the latest data on the palm oil industry issues. More efficient extension services are needed in meeting the need to increase knowledge. Information and Communication Technology (ICT) is the best method to accelerate agricultural technology transfer from research institutions to smallholders. Growing concerns about the impact of the covid-19 pandemic on health have prompted development agents to change the course and landscape of their delivery to social media application as a new norm socialisation agent. The study aims to examine the role of information and communication technology as a tool for developing new norms in conveying information and empowering smallholders’ knowledge. This study uses a qualitative approach through content analysis on several reports from the Malaysian Palm Oil Board (MPOB), Department of Statistics Malaysia (DOSM) and the Malaysian Communications and Multimedia Commission (MCMC). The study found that the use of social media platforms among Malaysians is high, thus the level of application of technology and palm oil information needs to be improved through social media applications. The government needs to develop social media applications that are friendly, easily accessible and the information presented is easy to understand. The implication of this study is that the use of information and communication technology will change the pattern of expansion of the palm oil sector in Malaysia in the future.